Conjugate mixed convection heat transfer with internal heat generation in a lid-driven enclosure with spinning solid cylinder. Issue 12 (December 2022) - Mahmud, Md. Jisan; Rais, Ahmed Imtiaz; Hossain, Md. Rakib; Saha, Sumon
Abstract: The current study investigates conjugate mixed convection heat transmission with internal heat generation in a square enclosure driven by a sliding lid and a solid cylinder with a heat-conducting surface at its center. The enclosure has a stationary bottom wall that is kept at a constant hot temperature and a cold upper wall that moves consistently. The solid cylinder rotates both clockwise and counterclockwise at different angular speeds. Two-dimensional steady continuity, momentum, thermal energy equations, and boundary and interface conditions are solved using a commercial CFD tool based on the finite element method. By choosing Reynolds, Grashof, and Richardson numbers, as well as varying the rotating cylinder's speed and direction under three different scenarios incorporating volumetric heat generation, parametric modeling of the mixed convection regime is carried out. The streamline and isotherm plots are used to illustrate qualitative findings. In contrast, the average Nusselt number, normalized Nusselt number, average drag coefficient, and average fluid temperature are used to assess quantitative thermal performance measures. This study reveals that the system's thermal performance is less dependent on the solid cylinder's rotational speed and direction. It successfully depicts the heat transfer enhancement with increasing Reynolds and Grashof numbers. A thorough study of the current facts can lead to the best choice of regulating parameters. Abstract : Conjugate heat transfer; Richardson number; Internal heat generation; Mixed convection; Rotating cylinder.